Measurement of Return on Asset (ROA) based on Comprehensive Income and its Ability to Predict Investment Returns: an Empirical Evidence on Go Public Companies in Indonesia before and during the Covid-19 Pandemic - Marhaendra Kusuma (Universitas Muhammadiyah Ponorogo, 2021)
Purpose - The concept of recognizing all inclusive income, which is used by IFRS and Indonesian SAK, is the basis for presenting other comprehensive income in the income statement. This change in format became the idea of developing a financial performance measurement.Methodology - Testing the effect of attributable comprehensive income ROA and attributable ROA net income on future cash flows and net income, as a proxy for the ability to provide future returns, and applying them in measuring performance before and during the Covid-19 pandemic.Findings - ROA net income is better able to predict future investment returns. ROA comprehensive income has more relevance value, when only other items of comprehensive income that have the potential to be realized are included. In assessing performance, users are advised to keep using the ROA of the net income version, and when using the ROA of the comprehensive income version, it is advisable to include only OCI which will be reclassified. The financial performance of companies in many industrial sectors experienced a decline during the Covid 19 pandemic using two ROA measures.Novelty - Development of ROA formulation by including other comprehensive income and profit attribution, so far ROA is only based on net income.